2008
DOI: 10.1021/jp801151k
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Hydrogen-Bond Structures and the C═O Stretching Frequencies of Carboxylic Acids as Studied by Density Functional Theory Calculations: Theoretical Basis for Interpretation of Infrared Bands of Carboxylic Groups in Proteins

Abstract: Carboxylic groups (COOH) of Asp and Glu side chains often function as key components in enzymatic reactions, and identifying their H-bond structures in the active sites is essential for understanding the reaction mechanisms. In this study, the correlation between the H-bond structures and the C=O stretching (nuC=O) frequencies of COOH groups was studied using density functional theory calculations. The nuC=O frequencies and their shifts upon OH deuteration were calculated for model complexes of acetic acid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 35 publications
9
89
0
Order By: Relevance
“…Consistent with bond elongation of C=O group, the stretching frequency is red shifted and the values, υ range between 12.57 to 94.68 cm −1 (table S22). The red shift of C=O stretching frequencies has also been reported by Takei et al in their DFT study on hydrogen bonded carboxylic acid· · · H-OR complexes 90. For example, when acetic acid accepts a proton from water or ethanol, its C=O bond length was lengthened by 0.007 Å and the shift of frequency was by −27 cm −1 from the free acetic acid.…”
supporting
confidence: 77%
“…Consistent with bond elongation of C=O group, the stretching frequency is red shifted and the values, υ range between 12.57 to 94.68 cm −1 (table S22). The red shift of C=O stretching frequencies has also been reported by Takei et al in their DFT study on hydrogen bonded carboxylic acid· · · H-OR complexes 90. For example, when acetic acid accepts a proton from water or ethanol, its C=O bond length was lengthened by 0.007 Å and the shift of frequency was by −27 cm −1 from the free acetic acid.…”
supporting
confidence: 77%
“…For such low vibrational energy to occur, the C=O group must interact with an H-bonding donor and the O-H group must be H-bonded to a strong acceptor (29,30). νC=O frequencies lower than 1,700 cm −1 have been reported for carboxylic groups only when the H-bonding donor is the NH 3 + group from a lysine (29, 30) or when the H-bond acceptor is a COO − group (43).…”
Section: Discussionmentioning
confidence: 99%
“…The groups accepting and donating the proton from and to the SB are yet unknown, but prime candidates are the terminal carboxylic groups of aspartate or glutamate residues and their corresponding acids as in other well-characterized rhodopsins. IR difference spectroscopy is particularly suited for the identification of protonation changes (26)(27)(28) because the C=O stretching vibration (νC=O) of protonated carboxylic groups appears in the 1,780 to 1,690 cm −1 frequency range (29,30). The vibrational bands in the carboxylic region of the four intermediate states exhibit significant spectral overlap ( ) bands were resolved (Fig.…”
Section: Proton Transfer and Hydrogen-bonding Changes Involving Asparmentioning
confidence: 99%
“…In contrast, the former signal showed that almost no dichroism, indicative of a nearly parallel orientation of the C=O bond. Assignment to COOH vibrations that show C=O bands in the similar region (Takei et al 2008) was dismissed by the observation of only minor downshifts (\2 cm -1 ) upon deuteration (Noguchi et al 1997) in comparison with an expected downshift by *10 cm -1 for a COOH group. From the significant difference in hydrogen bonding interactions and orientations between these two 13 2 -ester C=O groups, it was suggested that one of the signals originates from the 13 2 -ester C=O groups of P798, while the other is attributed to the ester C=O group of an adjacent pigment (Noguchi et al 1997).…”
Section: P798 In Heliobacteriamentioning
confidence: 99%